Spectroscopic studies of TeO2-ZnO-Er2O3 glass system - Sahar, Md Rahim; Sulhadi, K.; Rohani, M.S. (Springer Netherlands, 2007)
Series of glass based on the (80 − x)TeO2–20ZnO–(x)Er2O3 system (0.5 mol% ≤ x ≤ 2.5 mol%) has successfully been made by melt quenching technique. The optical properties of glass have been investigated by means of IR and Raman spectroscopy. It is observed that as the Er2O3 content is being increased, the sharp IR absorption peaks are consistently shifted from 650 to 672 cm−1 while the Raman shift intensity around 640–670 cm−1 is decreases but increases around 720–740 cm−1. It is found out that both phenomenons are related to the structural changes between the stretching vibration mode of TeO4 tbp and TeO3 tp, and bending vibration mode of Te–O bonds in the glass linkages.